2014
DOI: 10.1111/dmcn.12610
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance in self‐care and mobility after selective dorsal rhizotomy: a 10‐year practice‐based follow‐up study

Abstract: AIM To explore changes in performance in daily activities (self-care and mobility) 10 years after selective dorsal rhizotomy (SDR).METHOD Twenty-four children with bilateral spastic cerebral palsy were followed; the median age at SDR was 4 years 1 month (range 2y 5mo-6y 4mo) and at 10-year follow-up was 14 years 6 months (range 12y 3mo-16y 9mo). The preoperative Gross Motor Function Classification System (GMFCS) levels were: I (n=1), II (n=7), III (n=4), IV (n=11), and V (n=1). The Pediatric Evaluation of Disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…6 A high level of absolute agreement (96.8%) between the original and updated versions of the GMFCS has been shown. 7 Overall, the evidence supports that GMFCS levels remain stable over time, 4,[8][9][10][11][12] although the stability of the GMFCS in infants younger than 2 years is lower than at older ages. 13 For more than 20 years, children and adolescents with CP living in Sweden have participated in the Cerebral Palsy Follow-Up Programme (CPUP).…”
mentioning
confidence: 74%
“…6 A high level of absolute agreement (96.8%) between the original and updated versions of the GMFCS has been shown. 7 Overall, the evidence supports that GMFCS levels remain stable over time, 4,[8][9][10][11][12] although the stability of the GMFCS in infants younger than 2 years is lower than at older ages. 13 For more than 20 years, children and adolescents with CP living in Sweden have participated in the Cerebral Palsy Follow-Up Programme (CPUP).…”
mentioning
confidence: 74%
“…Peacock's original cohort has now been followed up for over 20 years and it is evident that the benefits they gained as children are still present (32). Nordmark et al and Josenby et al found that patients also had improvements in their Paediatric Evaluation of Disability Inventory (PEDI) scores, notably in the functional skills and mobility domains (27,31). Dudley et al found that these gains persisted to 15 years post-SDR (29).…”
Section: Outcome Of Sdrmentioning
confidence: 99%
“…Similarly, there was significant improvement in passive range of movement in hip, knee and ankle joints, as well as significant improvements in GMFM. In a 10-year follow-up study of 24 children, undertaken by the same group, additional improvement was evident in the functional skills, mobility and caregiver assistance (both self-care and mobility) domains of the Paediatric Evaluation of Disability Inventory (PEDI) scores between 5 and 10 years after SDR 12. This was particularly evident in children in the GMFCS I to III subgroups.…”
Section: Outcomes Of Selective Dorsal Rhizotomymentioning
confidence: 97%